Rôle des AOP fromagères dans la résilience des bassins laitiers de montagne en Suisse - Paul Donadieu de Lavit; Anouchka Bagnoud; Sirine Johnston; Marianne Milano; Dominique Barjolle (Revue de Géographie Alpine)
Mountain dairy regions in Switzerland have experienced a trajectory of adaptation to changing framework conditions over the past thirty years. Through interviews with farmers who witnessed the past, we traced the agricultural history of two contrasting Swiss dairy regions: the Franches-Montagnes in the canton of Jura and the Grand Entremont in the canton of Valais. We showed that the adoption of PDOs (Protected Designations of Origin) in 1992, the abolition of milk quotas in 1998, and the strengthening of interprofessional organizations have consolidated cheese production. The Franches-Montagnes have evolved towards a mixed production of industrial milk and cheese, notably Tête de Moine, thanks to innovations like the Girolle. The Grand Entremont, on the other hand, has maintained a dairy production focused on cheesemaking, with the PDO Raclette du Valais. The interprofessional organizations of PDO Raclette du Valais, Tête de Moine, and Gruyère have stabilized milk prices, promoting economic resilience, and established strict specifications enhancing the environmental sustainability of farms. These dairy regions remain vulnerable to climate change and heavily dependent on agricultural policy. They generate low incomes for farmers while requiring significant working hours, making it difficult to find successors to sustain mountain farming.